Hubungan Antara Stres dengan Kualitas Tidur Perawat COVID-19 di Ruang Perawatan - Yari, Yarwin; Ramba, Hardin La; Saragih, Dameria (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: Nurses are one of the health workers who are always in contact with Covid-19 patients, of course, they have a high enough risk of infection to be exposed to Covid-19. Objective: This study aimed to identify the relationship between stress and the quality of sleep of Covid-19 nurses in the Husada Hospital Jakarta treatment room. Methods: Quantitative research design with Cross-Sectional design, the number of samples in the study of 75 nurses working in the Covid-19 treatment room of Husada Hospital Jakarta, using the Depression Anxiety Stress Scale-21 research questionnaire and the Pittsburgh Sleep Quality Index (PSQI). Data analysis using Descriptive Statistics Crosstabs with the Chi-Square Test. Result: From the results of the study, it was found that the age distribution of the respondents was the most, namely nurses with < age of 35 years as many as 35 people (46.7%), the most gender, namely women, 71 (94.7%) nurses, the most working time of respondents was > 10 years, namely 41 people (54.7%). The most stress variables were mild stress 36 people (48%), normal 30 people (40%), and moderate 9 people (12%), based on sleep quality variables category no disturbance 71 people (94.7%), severe disorder 4 people (5.3%). The result of Correction Pearson Chi-Square was gotten a p-value of 0.000 (p<? 0.05). Conclusion: Stress in Covid-19 nurses is closely related to the quality of nurses' sleep. The lighter the stress experienced by the nurse, the better the quality of sleep. But the heavier the stress experienced by the nurses, the quality of sleep will be disturbed. Thus, it can be concluded that there is a relationship between stress and the quality of nurses’ sleep.